Heparin Vs Enoxaparin: Effects On D-Dimer And Hospital Stay In Covid-19 Patients - Fonny Cokro; Novita Suryamin; Dion Notario; Agnes Anania Triavika Sahamastuti; Catherine Keiko Gunawan; Anton Sumarpo (Jurnal Ilmu Kedokteran dan Kesehatan, 2026)
Elevated d-dimer levels due to venous thromboembolism and hypercoagulability in covid-19 patients play a role in disease severity and poor clinical outcomes. This study aims to compare the effectiveness of heparin and enoxaparin, two recommended anticoagulants, in reducing d-dimer levels and hospital stay duration in hospitalized covid-19 patients. This retrospective cohort study involved 106 hospitalized covid-19 patients with abnormal d-dimer levels treated between March 2020 and March 2023. The assessment included changes in d-dimer levels and hospitalization duration. Statistical analyses were performed using stata software. Patients receiving enoxaparin were 5.913 times more likely to experience a reduction in d-dimer levels compared to those receiving heparin (p=0.021). While smoking status (or=0.034; p=0.001) and the number of comorbidities (or=11.247; p=0.018) were notable factors influencing d-dimer reduction, enoxaparin administration was linked to significantly longer hospitalization (p=0.024). The severity of covid-19 also had a substantial impact on hospital stays, with severe (β = 5.757; p= 0.004) and critical (β = 9.147; p 0.001) cases requiring extended care. Thus, enoxaparin demonstrates greater efficacy in reducing d-dimer levels in hospitalized covid-19 patients, though at the cost of prolonged hospital stays.